Influence of Hydrological Factors on the Distribution of Methane Fields in the Water Column of the Bransfield Strait: Cruise 87 of the R/V “Academik Mstislav Keldysh”, 7 December 2021–5 April 2022 - Andrei Kholmogorov; Nadezhda Syrbu; Renat Shakirov (Water, 2022)
Within the framework of the expedition research “Complex studies of the Antarctic marine ecosystem in the areas of the transport and interaction of water masses in the Atlantic sector of Antarctica, the Scotia Sea and the Drake Strait” (cruise 87 of the R/V “Academik Mstislav Keldysh”, 7 December 2021–5 April 2022), the distribution of gas-geochemical fields of methane in the Bransfield Strait was studied in detail for the first time. The connection of the methane distribution in water with the complex hydrological regime of the strait has been revealed. Elevated values of methane concentrations brought to the Bransfield Strait in the warm current flow from the Bellingshausen Sea have been established. Low concentrations of methane also mark the cold waters of the Weddell Sea, which carry out the transit of water masses into the Atlantic Ocean. The research was carried out within the framework of the theme FWMM-2022-033 “Integrated environmental studies of the Southern Ocean” AAAA17-117030110035-4 and international obligations of the Russian Federation as a party to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources.